2021
DOI: 10.12659/msm.931050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes Following Anterior Cervical Discectomy and Fusion with Zero-Profile Anchored Spacer-ROI-C-Fixation and Combined Intervertebral Cage and Anterior Cervical Discectomy and Fusion: A Retrospective Study from a Single Center

Abstract: Background The aim of this study was to compare the outcomes following anterior cervical discectomy and fusion with zero-profile anchored spacer-ROI-C-fixation (ROI-C) vs combined intervertebral cage and anterior cervical discectomy and fusion (ACDF). Material/Methods We retrospectively analyzed 87 patients who underwent operations between January 2015 and January 2019, including 42 patients that underwent ROI-C treatment (group A) and 45 that were treated by the ACDF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Concerning cage subsidence, there was no significant difference between ZAS and PCC in bilevel ACDF. Our result is similar to the findings of He et al and Zhao et al, which may be inferred from the similar biomechanical properties of the two devices and similar fusion rates [ 43 , 47 ]. Overall, our findings suggested the adoption of ZAS in bilevel ACDF did not raise the incidence of cage sinking in comparison to PCC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning cage subsidence, there was no significant difference between ZAS and PCC in bilevel ACDF. Our result is similar to the findings of He et al and Zhao et al, which may be inferred from the similar biomechanical properties of the two devices and similar fusion rates [ 43 , 47 ]. Overall, our findings suggested the adoption of ZAS in bilevel ACDF did not raise the incidence of cage sinking in comparison to PCC.…”
Section: Discussionsupporting
confidence: 92%
“…Dysphagia remains the most commonly reported complication of ACDF and is often attributed to the introduction of anterior plates and oesophageal traction intraoperatively. Studies showed ZAS significantly minimised the incidence of postoperative dysphagia in ACDF [ 32 , 38 , 43 ]. Our results demonstrated that the postoperative dysphagia rate was significantly smaller in ZAS group than in PCC group in bilevel ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the intraoperative malfunctions relating to the ROI-C cage in the present study were due to breakage of the anchors, a complication that has not been previously described. Previous studies have assessed outcomes and postoperative complications following ACDF with the ROI-C cage and concluded that it was an acceptable alternative to the classic plate and cage constructs 24,25 . In aggregate, these data suggest that although these anchors frequently fail intraoperatively, they may not be associated with significant postoperative complications.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have assessed outcomes and postoperative complications following ACDF with the ROI-C cage and concluded that it was an acceptable alternative to the classic plate and cage constructs. 24,25 In aggregate, these data suggest that although these anchors frequently fail intraoperatively, they may not be associated with significant postoperative complications. Copyright r 2023 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Clinical Case Seriesmentioning
confidence: 77%
“…Several clinical studies have shown that the short-term outcome of SA cages is as good as that of conventional ACDF with a CPC. 6,7 However, there are few reports on its clinical efficacy, particularly with more than three years of follow-up evaluation.…”
mentioning
confidence: 99%